Heavy Metal Accumulation in the Highest Consumable Leafy Vegetables Normally Growing in the Moradabad District - Dr. Alka Rani; Abhinav Arun (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
The alloys using industry has a lot of waste material which were disposed randomly on ground as unauthorized disposal and leads to soil contamination. which were in addition to high polluted water due to heavy metal presence in the water used for irrigation and cleaning of the many leafy vegetables as spinach, Fenugreek, Chenopodium, coriander which were very often used in the food as source of nutrition in every day and every house despite of the fact that they were a lager accumulates of the heavy metal due to soil pollution and water pollution by these industry efflux.